2020
DOI: 10.1017/s0033291720000987
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal effects between daily situational perceptions and borderline personality symptoms in young adulthood: the role of childhood parenting experiences

Abstract: Background Recent research has emphasized the importance of within-person transactions between situational perceptions and borderline symptomatology. The current study extends current evidence by evaluating a broad range of situational perceptions and their transactions with borderline symptomatology across both private and professional contexts. Additionally, it explores whether early experiences of parental harsh punishment and emotional support during childhood, two well-established etiological factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Results demonstrated that approximately half of the variance in BPD symptoms was at the within‐person level, similar to previous research using composite measures of BPD pathology (Vanwoerden, Hofmans, & De Clercq, 2020) as well as single BPD symptoms or criteria (e.g. Scott et al., 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Results demonstrated that approximately half of the variance in BPD symptoms was at the within‐person level, similar to previous research using composite measures of BPD pathology (Vanwoerden, Hofmans, & De Clercq, 2020) as well as single BPD symptoms or criteria (e.g. Scott et al., 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, as the perception of the usefulness of parent training is one of the important factors in the intervention (Graf et al, 2014), it seems crucial for social workers to be able to provide training that is understandable for the parents and communicate the benefits. And indeed, programs aimed at increasing the quality of children's environment, focused on fostering the skills of parents, can have long-term benefits, such as the improvement of well-being of children in adulthood (Kiviniemi et al, 2020; Vanwoerden et al, 2021). For this reason, and in line with other authors’ work, we think it would be especially the role of practitioners, their competence, experience or training, that holds an important role in successful implementation of evidence-based parenting programs (Shapiro et al, 2015; Turner et al, 2011).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…A recent Finnish longitudinal study found that parental strictness during children's upbringing can eventually lead to higher levels of emotional distress, anxiety, or depression symptoms in adulthood (Kiviniemi et al, 2020). In addition, early experiences of a negatively perceived childhood environment or lack of emotional support are connected to personality disorders such as borderline personality disorder (Vanwoerden et al, 2021).…”
mentioning
confidence: 99%